2006
DOI: 10.1016/j.ccr.2006.05.026
|View full text |Cite
|
Sign up to set email alerts
|

The TSC2/mTOR pathway drives endothelial cell transformation induced by the Kaposi's sarcoma-associated herpesvirus G protein-coupled receptor

Abstract: The Kaposi's sarcoma-associated herpesvirus (KSHV), the infectious causative agent of Kaposi's sarcoma (KS), encodes a G protein-coupled receptor (vGPCR) implicated in the initiation of KS. Here we demonstrate that Kaposi's sarcomagenesis involves stimulation of tuberin (TSC2) phosphorylation by vGPCR, promoting the activation of mTOR through both direct and paracrine mechanisms. Pharmacologic inhibition of mTOR with rapamycin prevented vGPCR sarcomagenesis, while overactivation of this pathway was sufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
178
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 61 publications
3
178
0
4
Order By: Relevance
“…Consequently, the ORF45-induced RSK signaling becomes a crucial pathway involved in eIF4B phosphorylation during the viral lytic cycle (17). Interestingly, although ORF45 increased phosphorylation of both eIF4B and rpS6, we found that phosphorylation of eIF4B was not sensitive to rapamycin but that phosphorylation of rpS6 was, suggesting that eIF4B is phosphorylated by ORF45-activated RSK directly, whereas rpS6 is phosphorylated by mTOR/ S6K-dependent signaling that could be activated by RSK indirectly through phosphorylation of tuberous sclerosis protein 2 (55,58) or other KSHV gene products, such as viral G protein-coupled receptor or K1 (27)(28)(29)31). In any case, our data support the conclusion that the ORF45/RSK axis plays a crucial role in translational control during KSHV lytic replication through phosphorylation of eIF4B.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Consequently, the ORF45-induced RSK signaling becomes a crucial pathway involved in eIF4B phosphorylation during the viral lytic cycle (17). Interestingly, although ORF45 increased phosphorylation of both eIF4B and rpS6, we found that phosphorylation of eIF4B was not sensitive to rapamycin but that phosphorylation of rpS6 was, suggesting that eIF4B is phosphorylated by ORF45-activated RSK directly, whereas rpS6 is phosphorylated by mTOR/ S6K-dependent signaling that could be activated by RSK indirectly through phosphorylation of tuberous sclerosis protein 2 (55,58) or other KSHV gene products, such as viral G protein-coupled receptor or K1 (27)(28)(29)31). In any case, our data support the conclusion that the ORF45/RSK axis plays a crucial role in translational control during KSHV lytic replication through phosphorylation of eIF4B.…”
Section: Discussionmentioning
confidence: 73%
“…Kaposi sarcoma-associated herpesvirus (KSHV) is the etiological agent of endothelial neoplasm Kaposi sarcoma and two lymphoproliferative diseases, primary effusion lymphoma and multicentric Castleman disease. KSHV activates both MEK/ERK/RSK and AKT/mTOR/ S6K signaling pathways by multiple mechanisms (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). We recently found that the immediate early and tegument protein open reading frame 45 (ORF45) of KSHV interacts with RSK1 and RSK2 and causes sustained activation of RSK and ERK during lytic replication (17).…”
mentioning
confidence: 99%
“…Many of the classic proliferative signaling cascades are activated by kGPCR and are necessary for kGPCR tumorigenesis (13). Although the critical roles of the PI3K-AKT pathway in kGPCR tumorigenesis are emerging (14,15), the significance of other signaling pathways in kGPCR oncogenesis and mechanisms of signal transduction thereof remain poorly defined (e.g., NF-κB activation) (16). Despite the fact that NF-κB activation is well studied for its regulation in diverse physiological conditions, it remains unclear how kGPCR activates the NF-κB pathway in particular.…”
mentioning
confidence: 99%
“…Indeed, several studies show that mTOR regulated by Akt mediates transformation through multiple mechanisms including translational repression (Aoki et al 2001;Sodhi et al 2006) Importantly, the RAS/MAPK and PI3K/AKT pathways that both regulate mTOR and translation are among the most frequently altered pathways in cancer. mTOR activity is also regulated by oxygen deprivation and nutrient levels (Holcik and Sonenberg 2005).…”
Section: Microenvironments Affecting Translationmentioning
confidence: 99%